Dukungan Sosial dengan Prokrastinasi Akademik pada Mahasiswa yang Sedang Menyusun Skripsi - Fransiska Marisa Wening Kristanti; Christina Hari Soetjiningsih; Emmanuel Satyo Yuwono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Academic procrastination is the behavior of delaying the completion of academic tasks, commonly experienced by students and capable of negatively impacting academic achievement, particularly among those writing their theses. This study aims to examine the relationship between social support and academic procrastination among students. Employing a quantitative approach with a correlational design, the research involved 364 students selected via purposive sampling. Data were collected using questionnaires measuring social support and academic procrastination, then analyzed with Spearman's rho correlation test. The results reveal a significant negative relationship between social support and academic procrastination, with a correlation coefficient of -0.607 and a significance value of 0.000 (p < 0.01). This indicates that higher social support received by students correlates with lower levels of academic procrastination. Thus, it can be concluded that social support plays a crucial role in reducing academic procrastination behaviors among student.